The Effects of Rice Export Policy on Regional Income, Prices and the Poor : A 'Bottom-Up' Regional CGE Model for Vietnam - Kompas, Tom; Pham, Van Ha; Tuong, Nhu Che; Nguyen, Thi Minh Hoa; Bui, Trinh (World Bank, Washington, DC, 2017)
A 'bottom up' regional Computable General Equilibrium Model (CGE) model for Vietnam is constructed for 28 commodities and 8 regions (using a GSO input-output table for 2005). The model is used to analyze the recent dramatic increases in the world price of rice on the regional economy of Vietnam, and the Vietnamese policy response to limit exports. Although results show limited 'pro-poor' outcomes, the CGE model and a micro-simulation (using 2006 VHLSS - Vietnamese Household Living Standard Survey data) show that recent rice export quotas resulted in falls total rural savings as measured by the difference in total income less total production cost and consumption of rice. The structure of the paper is as follows. Section two provides the background and reviews existing studies in Vietnam that have tried to estimate the welfare impact of government policies in rice market. Section three describes the methods and data. The results from the CGE model and micro-simulation on household data are discussed in section four. Section five offer concluding remarks.